INFLUENCE OF NEW SPECIES AND DESIGN FUNCTIONS ON THE METHODOLOGY OF DESIGN EDUCATION ORGANIZATION - Швец, Елена (SWorldJournal, 2021)
Based on the analysis of research by scientists from different countries, the article defines new functions of design in the development of modern society. The emergence of new types of design is demonstrated. It is shown that new types and functions of